Comparison of filter media materials for heavy metal removal from urban stormwater runoff using biofiltration systems. (1st January 2015) - Lim, H.S.; Lim, W.; Hu, J.Y.; Ziegler, A.; Ong, S.L.
Abstract: The filter media in biofiltration systems play an important role in removing potentially harmful pollutants from urban stormwater runoff. This study compares the heavy metal removal potential (Cu, Zn, Cd, Pb) of five materials (potting soil, compost, coconut coir, sludge and a commercial mix) using laboratory columns. Total/dissolved organic carbon (TOC/DOC) was also analysed because some of the test materials had high carbon content which affects heavy metal uptake/release. Potting soil and the commercial mix offered the best metal uptake when dosed with low (Cu: 44.78 μg/L, Zn: 436.4 μg/L, Cd, 1.82 μg/L, Pb: 51.32 μg/L) and high concentrations of heavy metals (Cu: 241 μg/L, Zn: 1127 μg/L, Cd: 4.57 μg/L, Pb: 90.25 μg/L). Compost and sludge also had high removal efficiencies (>90%). Heavy metal leaching from these materials was negligible. A one-month dry period between dosing experiments did not affect metal removal efficiencies. TOC concentrations from all materials increased after the dry period. Heavy metal removal was not affected by filter media depth (600 mm vs. 300 mm). Heavy metals tended to accumulate at the upper 5 cm of the filter media although potting soil showed bottom-enriched concentrations. We recommend using potting soil as the principal media mixed with compost or sludge since these materials perform well and are readily available. The use of renewable materials commonly found in Singapore supports a sustainable approach to urban water management. Highlights: Heavy metal removal by soil, compost, coconut, sludge and commercial mix was tested. The heavy metals included Cu, Zn, Cd and Pb. Soil and commercial mix had the highest metal uptake out of the five materials. The depth of the material did not affect heavy metal removal. Most of the heavy metals accumulated in the top 5 cm of the materials tested.